Qualitative Analysis: Implementation of Teaching Factory Learning and Industry Partnerships to Improve Student Competency at Smk Karsa Mulya Palangka Raya - Rasmi Widya Rani; Budi Supriyatno; Aziz Hakim (Dinasti International Journal of Digital Business Management, 2025)
This study aims to analyze the implementation of Teaching Factory (TEFA) learning and industry partnerships, as well as their impact on improving the competence of students at SMK Karsa Mulya Palangkaraya in Central Kalimantan. Teaching Factory is a production-based learning approach that is oriented towards the world of work, emphasizing relevant and contextual practical skills. Industry partnerships involve collaboration between schools and the business and industrial sectors (DUDI) through field work practices (PKL), internships, curriculum development, and training. This study uses a qualitative method with a descriptive and correlational approach. Data were collected through observation, documentation, interviews, and academic records before and after the program implementation. The results show that the implementation of Teaching Factory learning and industry partnerships contributes positively to improving student competence, especially in practical skills and understanding of vocational subjects. There is a significant correlation between the level of industry involvement and the soft skills and hard skills of students. Therefore, integrating Teaching Factory learning and industry partnerships can be an effective strategy to improve the quality of vocational school graduates so that they are ready to work and professionally competent.